2018
DOI: 10.4330/wjc.v10.i11.242
|View full text |Cite
|
Sign up to set email alerts
|

Surgical left atrial appendage occlusion during cardiac surgery: A systematic review and meta-analysis

Abstract: AIMTo evaluate the safety and efficacy of surgical left atrial appendage occlusion (s-LAAO) during concomitant cardiac surgery.METHODSWe performed a comprehensive literature search through May 31st 2018 for all eligible studies comparing s-LAAO vs no occlusion in patients undergoing cardiac surgery. Clinical outcomes during follow-up included: embolic events, stroke, all-cause mortality, atrial fibrillation (AF), reoperation for bleeding and postoperative complications. We further stratified the analysis based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…19,20 We terminated anticoagulation not earlier than after 6 months of FREEAF as we were aware of endocardial, wound-associated thromboembolism. Similar to a former meta-analysis, 25 we had no evidence for stroke, peripheral thromboembolism, or bleeding disorders. Thus, another benefit to FAP patients is the termination of anticoagulation.…”
Section: Discussionmentioning
confidence: 71%
“…19,20 We terminated anticoagulation not earlier than after 6 months of FREEAF as we were aware of endocardial, wound-associated thromboembolism. Similar to a former meta-analysis, 25 we had no evidence for stroke, peripheral thromboembolism, or bleeding disorders. Thus, another benefit to FAP patients is the termination of anticoagulation.…”
Section: Discussionmentioning
confidence: 71%
“…We did not identify any differences between the groups regarding in-hospital complications, similar to previous studies. [ 11 , 13 , 27 ] However, our results showed that SLAAO was associated with longer length of stay, and longer CPB and aortic cross-clamp times, suggesting that this technique may still increase the burden of perioperative complications, to some extent.…”
Section: Discussionmentioning
confidence: 78%
“…[ 5 , 19 ] However, there is no conclusive evidence that SLAAO reduces stroke risk in patients with atrial fibrillation undergoing cardiac surgery. Recently, several retrospective studies [ 9 , 10 , 20 ] and meta-analyses [ 11 13 ] showed that SLAAO is associated with a lower incidence of ischemic stroke or systemic embolism and mortality in patients undergoing cardiac surgery. Friedman et al [ 10 ] published a retrospective study involving 10,524 patients aged ≥65 years with atrial fibrillation undergoing cardiac surgery and found that SLAAO was associated with a significantly lower risk of readmission for thromboembolism and all-cause mortality during a 3-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Success rates vary according to surgical procedure with highest success with excision/amputation techniques 78 . A recent meta‐analysis concluded that surgical LAAO was associated with a lower risk of thromboembolic events and stroke 79 . In a retrospective cohort of 75,782 adults with LAAO during cardiac surgery, with 29% women, the hazard ratio for stroke was higher in women [0.80 (0.51–1.25)] than men [0.59 (95% CI, 0.39–0.91)] among propensity‐matched patients with AF at baseline 80 .…”
Section: Stroke Prevention In Af‐sex Differences In Stroke Riskmentioning
confidence: 99%